PREDICTIVE FACTORS FOR FAILURE OF FIRST RADIOACTIVE IODINE THERAPY IN PATIENTS WITH HYPERTHYROIDISM - Murthy, Tilagamaty; Shander, Shubash; Lim, Lee Ling; Vethakkan, Shireene; Paramasivam, Sharmila (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Radioactive iodine (RAI) therapy is used commonly and successfully as a definitive treatment for hyperthyroidism. Predictive factors for RAI outcomes have been previously shown to be heterogenous. This study aimed to examine the prevalence of treatment failure at one year post-RAI as well as identify the predictors of RAI failure in our local urban population. METHODOLOGY We performed a retrospective study involving patients who had undergone first RAI therapy from January 2015 to December 2020 in the University Malaya Medical Centre. Pre- and post-RAI data were collected from electronic medical records, including demographics, goiter size, thyroid function tests at diagnosis/pre-RAI, RAI dose, anti-thyroid drug duration and dose, and time taken to achieve euthyroidism or hypothyroidism. Data were analyzed using SPSSⓇ version 23 and expressed as mean/median or frequencies, and multivariate analysis using logistic regression. RESULTS A total of 292 patients were included in the study. Majority of the patients were female (69.9%) with Graves’ disease (79.2%). The median RAI dose given was 16 mCi (range, 10-18). Within one year of RAI, 85.3% of patients achieved treatment success; of these, 93.2% attained success within six months. Treatment failure, defined as persistent hyperthyroidism one year post-RAI, was seen in 14.7%. We found that a high serum free T4 at diagnosis was a predictive factor for RAI failure (OR 1.01; 95% CI, 1.01-1.02; p=0.002). There were no significant associations between age, gender, body mass index, goiter size and RAI dosage with failure of RAI in our study population. CONCLUSION High serum free T4 at diagnosis was associated with poorer RAI outcomes. Higher doses of RAI or thyroidectomy may be considered in these patients